Long-term effects of allergen-specific subcutaneous immunotherapy for house dust mite induced allergic rhinitis. Issue 11 (17th October 2017) - Sahin, E; Dizdar, D; Dinc, M E; Cirik, A A
Abstract: Background: Allergic rhinitis is strongly associated with the presence of house dust mites. This study investigated the long-term effects of allergen-specific immunotherapy. Allergen-specific immunotherapy was applied over three years. The study was based on a 10-year follow up of patients with allergic rhinitis. Methods: The study was conducted between 2001 and 2015. Skin prick test results and symptom scores were evaluated before (26 patients) and after 3 years (20 patients) of allergen-specific immunotherapy (using data from a previously published study), and 10 years after allergen-specific immunotherapy had ended (20 of 26 patients). Results: The symptom scores before allergen-specific immunotherapy were significantly higher than those obtained after 3 years of allergen-specific immunotherapy and 10 years after allergen-specific immunotherapy ( p < 0.0175). There were no significant differences between the scores obtained at 3 years and 10 years after allergen-specific immunotherapy ( p > 0.0175). Conclusion: Subcutaneous immunotherapy is an effective treatment for house dust mite induced allergic rhinitis.